1986
DOI: 10.1002/ajim.4700090408
|View full text |Cite
|
Sign up to set email alerts
|

Acquired intolerance to organic solvents and results of vestibular testing

Abstract: Among 160 consecutive patients referred to the Clinic of Occupational Medicine, Rigshospitalet, for symptoms connected with exposure to organic solvents, 20 exhibited symptoms of acquired intolerance to minor amounts of organic solvents. Later, an additional 30 consecutive patients with symptoms of acquired intolerance were included, yielding a total of 43 men and 7 women. The characteristics of the clinical syndrome described are complaints of dizziness, nausea, and weakness after exposure to minimal solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…This syndrome, caused by the neurotoxic properties of solvents, has been described as causing symptoms of dizziness, nausea, weakness, intoxication, incoordination, exhilaration, sleepiness, stupor, early anesthesia, visual disorders, sleep apnea and insomnia, alterations in cognitive functioning, personality changes, fatigue, irritability, loss of appetite, problems with arm strength, and feeling ''high.'' [Gyntelberg et al, 1986;Dick, 1988;Takeuchi, 1988;Monstad et al, 1987;Lindelof et al, 1992;Morrow et al, 1990;Fidler et al, 1987]. While solvent syndrome has been well described, its physiological processes remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome, caused by the neurotoxic properties of solvents, has been described as causing symptoms of dizziness, nausea, weakness, intoxication, incoordination, exhilaration, sleepiness, stupor, early anesthesia, visual disorders, sleep apnea and insomnia, alterations in cognitive functioning, personality changes, fatigue, irritability, loss of appetite, problems with arm strength, and feeling ''high.'' [Gyntelberg et al, 1986;Dick, 1988;Takeuchi, 1988;Monstad et al, 1987;Lindelof et al, 1992;Morrow et al, 1990;Fidler et al, 1987]. While solvent syndrome has been well described, its physiological processes remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of mechanisms have been proposed to explain the triggering of symptoms by levels ofexposure that have been historically considered toxicologically trivial. These mechanisms include "acquired intolerance" [to pesticides (52) or solvents (53)], "olfactory vertigo" (54), "psychological sensitization" (55), "panic disorder (in response to solvents)" (56).…”
Section: Behavioral Sensitization To Odorantsmentioning
confidence: 99%
“…For odor exposure, the EPA (1991) study showed that, in buildings, at least two types of odor exposure (that from fresh paint, glue, etc., and body odor) were strongly associated with SBS symptoms. Exposure to odorous substances was reported to result in symptoms such as dizziness, nausea, and weakness (Gyntelberg et al 1986). Inclusion of odor as an explanatory variable in the analysis of air quality increased the proportion of variance explained (R 2 ) from 0.34 to 0.56 acutely, 0.37 to 0.52 sub-acutely, and 0.09 to 0.22 after the exposure (Mølhave et al 1993).…”
Section: Introductionmentioning
confidence: 98%